1996
DOI: 10.1093/protein/9.7.559
|View full text |Cite
|
Sign up to set email alerts
|

Native-like β-hairpin structure in an isolated fragment from ferredoxin: NMR and CD studies of solvent effects on the N-terminal 20 residues

Abstract: The conformational properties of protein fragments have been widely studied as models of the earliest initiation events in protein folding. While native-like alpha-helices and beta-turns have been identified, less is known about the factors that underly beta-sheet formation, in particular beta-hairpins, where considerably greater long-range order is required. The N-terminal 20 residue sequence of native ferredoxin I (from the blue-green alga Aphanothece sacrum) forms a beta-hairpin in the native structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
68
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 2 publications
6
68
0
Order By: Relevance
“…They also are structures found in many naturally occurring bioactive cyclic peptides such as gramicidin S and the peptide hormones oxytocin and vasopressin. Importantly, several studies have demonstrated the stability of an isolated -hairpin [21][22][23][24][25][26][27][28] and, from these studies, considerable insight has been obtained into the factors that contribute to the conformational energetics. Cross-strand interactions are key and may include aromatic-aromatic, 29 charge-charge electrostatic, 30 or hydrophobic packing interactions.…”
Section: The B-hairpinmentioning
confidence: 99%
“…They also are structures found in many naturally occurring bioactive cyclic peptides such as gramicidin S and the peptide hormones oxytocin and vasopressin. Importantly, several studies have demonstrated the stability of an isolated -hairpin [21][22][23][24][25][26][27][28] and, from these studies, considerable insight has been obtained into the factors that contribute to the conformational energetics. Cross-strand interactions are key and may include aromatic-aromatic, 29 charge-charge electrostatic, 30 or hydrophobic packing interactions.…”
Section: The B-hairpinmentioning
confidence: 99%
“…Studies of isolated, water-soluble -hairpins can provide valuable insight into properties of -sheet structure and folding since -hairpins are considered to act as possible nucleation sites for protein folding. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Additionally, their detailed structural interactions can be relevant in developing an understanding of the mechanism for forming various -sheet structures such as found in many (amyloid-like) neurodegenerative diseases in which protein aggregation is an important pathology. [15][16][17][18] During the past decade, there have been many reports discussing de novo designed, water-soluble -hairpin peptide systems, as well documented in several reviews.…”
mentioning
confidence: 99%
“…In spite of this, some linear peptides have recently been shown to fold into monomeric b-hairpins in aqueous solutioñ Blanco et al, 1998;Maynard et al, 1998;Smith & Regan, 1997! or alcohol-water mixtures~Cox et al, 1993Blanco et al, 1994;Searle et al, 1996!. Furthermore, the design and structure elucidation of model b-hairpins has demonstrated that the conformation of the turn plays a key role in directing b-hairpin structure~de Alba et al, 1996Alba et al, , 1997aHaque & Gellman, 1997!.…”
mentioning
confidence: 99%